2015
DOI: 10.18552/joaw.v5i1.168
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Titles and Disciplinary Conventions: A Corpus Study of Eight Disciplines

Abstract: Research articles are clearly influenced by the discipline of the research being reported. Just as disciplinary conventions place constraints on, for example, the moves and language use of abstracts and introductions, they also provide a set of options for title design. This study attempts to identify the title conventions of eight disciplines by focusing on various features that play a part in title design: the use of multiple-unit titles (those with subtitles); the use of noun phrases to form the title; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 11 publications
1
35
4
4
Order By: Relevance
“…Interestingly, we found that not only the authors follow one another in their title choices (Nagano, 2015) within disciplines but that certain trends emerged in a whole range of disciplines at the same time. This is worth further study.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Interestingly, we found that not only the authors follow one another in their title choices (Nagano, 2015) within disciplines but that certain trends emerged in a whole range of disciplines at the same time. This is worth further study.…”
Section: Discussionmentioning
confidence: 84%
“…For the first role, the words are chosen to "convey credible information for a given population of producer-readers" (Callon et al, 1983, p. 199). Thus, the choice of words is a negotiation process reflecting both the behavior of individual authors and scholarly collectives (Hyland, 2004(Hyland, , 2012Nagano, 2015). Authors choose particular words to denote their alliance with particular communities, sub-communities, and lines of thought.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In view of this, titles have been studied from varied perspectives, in terms of title length (e.g., Afful, 2017;Hudson, 2016), the effects of title form and length on the rate of citation (e.g., Fox & Burns, 2015;Jamali & Nikzad, 2011;Whissell, 2013), syntactic organisation (e.g., Afful, 2017;Cheng et al, 2012), diachronic lens (e.g., Rahman & Hussein, 2016) or informativity/semantic content (e.g., Afful, 2017;Rahman & Hussein, 2016). There are other studies which have focused on a single discipline (e.g., Cheng et al, 2012;Wang & Bai, 2007;Whissell, 1999) or multidiscipline (e.g., Fortanet et al, 1997;Haggan, 2004;Nagano, 2015). Although literature shows that titles have been studied from macro or microstructure levels in individual disciplines (e.g., Cheng et al, 2012) and cross-disciplinary perspectives (e.g., Fortanet et al, 1997;Haggan, 2004), detailed investigation of RA title syntactic structures appears inadequate.…”
Section: Introductionmentioning
confidence: 99%